2011
DOI: 10.1111/j.1365-2214.2011.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of community paediatric outpatient referrals 2006

Abstract: This population-based study gives a unique insight into the epidemiology of referrals to community paediatricians in the UK in 2006 and how these differ from those recorded in a different UK district in 1998.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Paediatricians identify barriers to undertaking rural practice as increased workload, longer working hours, social isolation, insufficient financial incentives and an increasing trend towards subspecialisation 4 . Despite the smaller population base in rural communities, there is a demonstrated need for paediatric services, with our previous work finding the referral rate for the initial year of this rural paediatric service was 31.6 per 1000, 6 which is significantly higher than previously reported referral rates 7–9 …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Paediatricians identify barriers to undertaking rural practice as increased workload, longer working hours, social isolation, insufficient financial incentives and an increasing trend towards subspecialisation 4 . Despite the smaller population base in rural communities, there is a demonstrated need for paediatric services, with our previous work finding the referral rate for the initial year of this rural paediatric service was 31.6 per 1000, 6 which is significantly higher than previously reported referral rates 7–9 …”
Section: Introductionmentioning
confidence: 80%
“…This study aimed to build on our previous work that identified the referral and triage patterns during the initial year of the service by describing the types of problems diagnosed at the initial appointment and associated outcomes. Collection and analysis of this data is essential for health service planning, facilitating the identification of areas of need within specific communities to support contextualised delivery of paediatric health care 1,8 . Improving the integration and coordination of the finite paediatric services in rural communities has been deemed imperative as there are a myriad of influences on children's development that no paediatric service in isolation can effectively manage 1…”
Section: Introductionmentioning
confidence: 99%
“…The Australian health-care system, similar to other countries, is continuously trying to manage childhood conditions within a primary health-care setting. 21,22 The continual education of primary care providers to support children's complex developmental needs, both prior to and following specialist care, is a contemporary topic of discussion. 23 Results of this study highlight this need by the proportion of children who did not receive a diagnosis and were discharged back to GP care following AAHP input.…”
Section: Discussionmentioning
confidence: 99%
“…While all of these studies demonstrate a clear association between peer reinforcement and increased deviant behavior, the limited work on elementary school-age children is surprising. Further examination of peer reinforcement for deviant behavior is vital in this population, as elementary school is commonly a time when children are referred for mental health services, most often for behavior problems (Thompson & Bhrolchain, 2011). …”
Section: Effects Of Behavior Modification and Stimulant Medication Onmentioning
confidence: 99%